The effect of negative income shocks on pensioners - Julian Johnsen; Alexander Willén (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
This paper provides novel evidence on the labor supply response to negative income shocks in retirement, exploiting an institutional feature that caused differential and unexpected income losses among otherwise identical individuals in a sharp regression discontinuity design. We conclude that retired pensioners do not return to work despite income losses of up to seven percent of their annual income. The paper further shows that the negative income shock had no impact on the health of pensioners. At the height of an ongoing global crisis in which public pension funds are rapidly losing value, these results may be particularly important.
Keywords: I38; J14; J26; 330; Pension Policy; Retirement; Labor Supply; Health